ASKEW POSITIONS—SCHIEFLAGEN: DEPICTIONS OF CHILDREN IN GERMAN TERRORISM FILMS (Revue D’études Interculturelles De L’image, 2014)
This essay discusses the appearance of children in films that negotiate the legacies of West left-wing German and global terrorism. The four films discussed in this essay depict children in Schieflagen (askew positions), but use these images to create rather different political messages. InDeutschland im Herbst (1978), Die bleierene Zeit(1981) and Innere Sicherheit (2000), children are melodramatic devices that convey a sense of national tragedy, nostalgia for “innocence,” and/or a nationally coded sense of hope. As opposed to representing such an uncanny mixture between melodramatic victim and national symbol, children in the recent film collaborationDeutschland 09 (2009) are the face of the present. Deutschland 09 depicts children as disconnected from German history, which relieves them of the burden of national representation and, as a result, offers a potential for a less normative and more diverse perspective on Germany’s history and present. While their missing connection to national history leaves them to appear detached and confused, this confusion can be read as a search for different understandings of history and belonging in twenty-first century Germany.